2022
DOI: 10.3389/fmicb.2022.1000222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the application of vermicompost and millicompost humic acids about the soybean microbiome under water restriction conditions

Abstract: Humic substances (HSs) are constituent fractions of organic matter and are highly complex and biologically active. These substances include humic acids (HA), fulvic acids (FA), and humin. HS are known to stimulate the root system and plant growth and to mitigate stress damage, including hydric stress. Humic acids have already been reported to increase microbial growth, affecting their beneficial effect on plants. However, there is scarce information on whether HA from vermicompost and millicompost, along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Da Silva et al [12] showed that the application of humic acids could help soybean growth through its interference with the endophytic bacteria community, triggering the enrichment of microorganisms with the potential to act both on plant growth and defense against pathogens and abiotic stresses. The modulation of the endophytic and rhizosphere community by humic acids was previously described and can be depicted as a complex process that emerges from different interrelationships between components and functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Da Silva et al [12] showed that the application of humic acids could help soybean growth through its interference with the endophytic bacteria community, triggering the enrichment of microorganisms with the potential to act both on plant growth and defense against pathogens and abiotic stresses. The modulation of the endophytic and rhizosphere community by humic acids was previously described and can be depicted as a complex process that emerges from different interrelationships between components and functions.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports have also documented a substantial Increase in soybean root dry matter due to HSs, although there was no corresponding increase in the number of nodules [11]. However, more recent studies have shown that soybean plants treated with humic acids can promote plant growth and nodulation compared to control plants by stimulating the abundance of bacterial species in roots [12]. HS' modulation of the rhizosphere community was attributed to the increasing exudation of sugars [13] and other available organic compounds [14].…”
Section: Introductionmentioning
confidence: 95%
“…Hungria and Mendes [41] reported that the establishment of soybean in Brazil through the inoculation of Bradyrhizobium strain successfully improved the crop yield and amount of nitrogen fixation. Humic substances from vermicompost have complex and bioactive materials which include humic acids, fulvic acid and humin strongly stimulate the rhizospere and growth of the plant tolerate stress damage including water stress [42]. Humic substances are constituent fractions of organic matter and are highly complex and biologically active.…”
Section: Growth Parameters Of Soybeanmentioning
confidence: 99%